The Effect of Different Irrigation Protocols for Smear Layer Removal on Bond Strength of a New Bioceramic Sealer - Shokouhinejad, Noushin; Hoseini, Atefeh; Gorjestani, Hedayat; Shamshiri, Ahmad Reza (Iranian Endodontic Journal, 2013)
Introduction: The purpose of this study was to assess the effect of different irrigation protocols for smear layer removal on the bond strength of EndoSequence BC Sealer, a new bioceramic sealer, to root canal dentin. Materials and Methods: The middle third of forty-four extracted human teeth were sectioned horizontally to obtain 128 dentin disks. After standardization of canal spaces, dentin disks were immersed in 5.25% NaOCl for 20 min. The specimens were then randomly assigned to four groups (n=32) according to dentin treatment procedure: group 1, 17% EDTA (1 min); group 2, 17% EDTA (1 min) + 5.25% NaOCl (5 min); group 3, 17% EDTA (1 min) + 2% chlorhexidine (CHX) (5 min); and group 4, 17% EDTA (1 min) + saline (5 min). After dentin treatment, two specimens of each group were prepared for investigation with scanning electron microscopy (SEM). Surface of root canal wall was assessed in each specimen. Then the canal spaces were filled with EndoSequence BC Sealer in the remaining specimens. Push-out bond-strength and failure modes were assessed. The data on push-out test were analyzed using one-way ANOVA test. The significance level was set at P=0.05. Results: There was no significant difference between the bond strengths of test groups (P=0.203). The bond failure was mainly cohesive for all groups. Conclusion: Under the conditions of this ex vivo study, it could be concluded that the application of 17% EDTA alone or followed by 5.25% NaOCl, 2% CHX, or saline resulted in similar bond strength of EndoSequence BC Sealer to dentinal walls.